2007
DOI: 10.1021/ac061370u
|View full text |Cite
|
Sign up to set email alerts
|

TOF-SIMS 3D Biomolecular Imaging of Xenopus laevis Oocytes Using Buckminsterfullerene (C60) Primary Ions

Abstract: Time-of-flight secondary ion mass spectrometry (TOF-SIMS) using buckminsterfullerene (C60) as the primary ion source has the ability to generate chemical images of surfaces with high sensitivities and minimal chemical damage. We studied the application of C60+ to depth profile a biological cell surface in a controlled manner and to subsequently image the revealed subsurfaces, in order to generate three-dimensional molecular images of the biological system. Such an analytical tool not only enables the surface l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
271
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 288 publications
(275 citation statements)
references
References 40 publications
3
271
0
1
Order By: Relevance
“…We have used a standard cellular proliferation assay to measure the effects of the various washing solutions on cell viability. These results may indicate why this technique has been reported as successful by others [14,24].…”
Section: Resultsmentioning
confidence: 57%
See 3 more Smart Citations
“…We have used a standard cellular proliferation assay to measure the effects of the various washing solutions on cell viability. These results may indicate why this technique has been reported as successful by others [14,24].…”
Section: Resultsmentioning
confidence: 57%
“…We have therefore undergone an extensive search for a washing solution which will both clean the cells sufficiently and preserve the maximum possible amount of cellular information for analysis. Recent investigations [14,24] have reported using pure deionized water to wash cells prior to drying and imaging MS analysis. In our laboratory, however, we have found that washing with water, even for as few as 10 seconds, can cause a loss of cellular integrity during the washing step.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent advances in both ionization efficiency (polyatomic primary ions) and sample preparation have significantly improved the sensitivity for detecting intact, medium-sized molecular ions (Ͻ1000 Da) from tissues and cells [1][2][3][4][5][6]. High-resolution images of small peptides, lipids, cholesterol, vitamins, and pharmaceuticals have all been reported, and through the use of large polyatomic primary ions three-dimensional (3D) molecular imaging results are beginning to appear [7][8][9].The images are normally created by moving the ionization beam in a set pattern across the sample and performing mass analysis at each point of the raster (spatially correlated mass spectrometry). The raster pattern typically uses 8-or 10-bit encoding; as a result the maximum analysis field contains 256 ϫ 256 (or 1024 ϫ 1024) pixels.…”
mentioning
confidence: 99%